Perceiving in depth. Volume 2, Stereoscopic vision - Howard, Ian P.; Rogers, Brian J. (Oxford : Oxford University Press, 2012)
This volume looks at mechanisms of depth perception by all senses, including aural, electrosensory organs, and the somatosensory system. It reviews stereoscopic vision.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Depth perception